(untitled) (Research, Society and Development, 2023)
To analyze how the Shantala massage method can contribute to the strengthening of the mother-child bond. This is a descriptive study, with a qualitative approach, carried out in Family Health Units in the city of Santarém/PA. Data collection was carried out through semi-structured interviews, aimed at mothers who agreed to use the Shantala massage method on their babies. It is noteworthy that the ethical aspects related to research involving human beings were considered for the study. The study participants were 6 mothers with their respective babies, the age of the babies ranged from 1 to 4 months and the majority were female. Among the feelings present during the application of Shantala massage, the feeling of protection, the feeling of dedication and the feeling of recognition and satisfaction stood out. Regarding the sensations presented by the baby when being touched, the mothers reported the sensations of "joy", "protected", "relaxed, happy and smiling". The main physiological changes observed in the babies were: relief of colic, improvement in intestinal functioning and improvement in sleep pattern. In addition, mothers could perceive emotional changes such as: tranquility, improved bonding, relaxation and improved sociability. It was evidenced that the application of the Shantala technique resulted in positive feelings for the mother-child binomial. Massage provided a positive experience through the exchange of affection and affection, which contributes to strengthening the bond between mother and baby, as a result of greater approximation and contact.